2003
DOI: 10.1073/pnas.0836953100
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection affects local extinction and turnover in bird communities

Abstract: Predicting extinction risks has become a central goal for conservation and evolutionary biologists interested in population and community dynamics. Several factors have been put forward to explain risks of extinction, including ecological and life history characteristics of individuals. For instance, factors that affect the balance between natality and mortality can have profound effects on population persistence. Sexual selection has been identified as one such factor. Populations under strong sexual selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
110
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 42 publications
7
110
4
Order By: Relevance
“…O ur understanding of sexual selection is obstructed by lack of progress on a fundamental question: How do we measure sexual selection rigorously, and how do we compare its strength between the sexes or across taxa (1-3)? Sexual selection underlies some of the most extreme traits in nature, including spectacular armaments and ornaments, and affects macroevolution via both speciation and extinction (4)(5)(6)(7)(8). It is thought to vary systematically with a species' mating system (i.e., the degree of multiple mating by each sex) and with sex-specific investment in offspring and mating partners (i.e., parental investment and direct benefits) (9,10).…”
mentioning
confidence: 99%
“…O ur understanding of sexual selection is obstructed by lack of progress on a fundamental question: How do we measure sexual selection rigorously, and how do we compare its strength between the sexes or across taxa (1-3)? Sexual selection underlies some of the most extreme traits in nature, including spectacular armaments and ornaments, and affects macroevolution via both speciation and extinction (4)(5)(6)(7)(8). It is thought to vary systematically with a species' mating system (i.e., the degree of multiple mating by each sex) and with sex-specific investment in offspring and mating partners (i.e., parental investment and direct benefits) (9,10).…”
mentioning
confidence: 99%
“…The basic idea is that sexual selection can easily cause populations to diverge in mate recognition systems, thus leading to rapid evolution of prezygotic barriers between populations (22). Interestingly, the results of Doherty et al (1) suggest that an increased local extinction rate is not necessarily translated into an overall loss of sexually selected species. In their study covering a 21-year time span, a higher turnover rate of these species was found to compensate for the increased local extinction rate.…”
mentioning
confidence: 83%
“…However, occasionally the two fields do meet, as in the article by Doherty et al (1) in this issue of PNAS, in which the authors interpret new and exciting results obtained through statistical analysis of ecological monitoring data (2) within the framework of sexual selection (3). Through a powerful statistical analysis of data collected by volunteers, the authors are able to show, at a continent-wide scale, that sexual selection is associated with higher local extinction and turnover rates in natural bird communities, which affects biodiversity across the continent (Fig.…”
mentioning
confidence: 87%
See 2 more Smart Citations